Multipath exploitation for enhanced defect imaging using Lamb waves. (December 2017) - Golato, Andrew; Ahmad, Fauzia; Santhanam, Sridhar; Amin, Moeness G.
Abstract: This paper presents a multipath exploitation approach for defect imaging in thin-walled structures using Lamb waves under the sparse reconstruction framework. An image of the defects in the region of interest is obtained by inverting a multipath propagation model via group sparse reconstruction. This permits accurate imaging of regions close to the structure boundary without the introduction of 'false' defects or ghosts. Real-data measurements of defects close to the edge of an aluminum plate are used to demonstrate the effectiveness of the multipath exploitation scheme. Highlights: Propose Lamb wave-based Structural health monitoring scheme that inverts model-based dictionaries to reproduce an image of a region of interest thereby localizing any damage present. Multipath propagation model accounts for boundary reflections enhancing localization accuracy when defects are located near the plate edges. Utilize sparse reconstruction for model inversion, which acknowledges that the problem is defect-sparse. Apply group sparsity constraint, which performs reconstruction jointly across all multipaths. Experimental validation using an aluminum plate is provided.